20.3k views
3 votes
If f(x) = 3(-2x + 7) , find f(13)

f(13) =

User JordyvD
by
5.1k points

1 Answer

3 votes

Answer:

f(13) = -57

Explanation:

We are given the function f(x) = 3(-2x + 7) and asked to find the value at f(13). Substitution means to replace an unknown value with a known one in order to solve a problem. We can do this by substituting the value of 13 for the x-value in the function.

f(13) = 3(-2(13) + 7)

f(13) = 3(-26 + 7)

f(13) = 3(-19)

f(13) = -57

Therefore, because this question is asking us to find only the value at f(13), we have determined that f(13) = -57.

User Jaco Van Niekerk
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.